2018
DOI: 10.1073/pnas.1812016115
|View full text |Cite
|
Sign up to set email alerts
|

Left/right asymmetric collective migration of parapineal cells is mediated by focal FGF signaling activity in leading cells

Abstract: SignificanceThe ability of cells to migrate collectively underlies many biological processes. The parapineal is a small group of cells that requires Fgf8 to migrate from the midline to the left side of the zebrafish forebrain. Studying the dynamics of FGF pathway activation reveals that FGF activity is restricted to a few left-sided parapineal cells. Global activation of the FGF pathway interferes with parapineal migration in wild-type embryos, while focal activation in few parapineal cells can restore migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…This is supported by our observation that the onset of sox1a expression in the migrating parapineal is asymmetric, starting at the left (leading) side. In accordance with parapineal migration being a collective behaviour (Roussigné et al, 2018), our parapineal transplant experiments suggest that single parapineal cells do not migrate effectively to their final destination but rather stay close to the site of transplantation. However, regardless of the transplant position, left dHb character is nevertheless induced.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is supported by our observation that the onset of sox1a expression in the migrating parapineal is asymmetric, starting at the left (leading) side. In accordance with parapineal migration being a collective behaviour (Roussigné et al, 2018), our parapineal transplant experiments suggest that single parapineal cells do not migrate effectively to their final destination but rather stay close to the site of transplantation. However, regardless of the transplant position, left dHb character is nevertheless induced.…”
Section: Discussionsupporting
confidence: 80%
“…It is not clear whether parapineal cells exhibit any heterogeneity regarding their ability to induce left dHb character nor whether direct cell-cell contact is required between the parapineal and the left dHb. A recent study demonstrated focal activation of FGF-signalling in leading cells of the migrating parapineal, indicating that cells possess positional identity within the parapineal (Roussigné et al, 2018). This is supported by our observation that the onset of sox1a expression in the migrating parapineal is asymmetric, starting at the left (leading) side.…”
Section: Discussionmentioning
confidence: 99%
“…The last two decades have produced significant progress in understanding the morphogenetic processes that lead to consistent left-right asymmetries within the nervous system 52 , and the mechanisms by which stochastic neuroanatomical asymmetry emerges when normal lateralizing cues are experimentally removed 53 . Moreover, work in Caenorhabditis elegans has provided important insights into the mechanisms that underlie stochastic acquisition of left-right neuronal identity 54 .…”
Section: Discussionmentioning
confidence: 99%
“…With this work, we have provided a small step towards unifying competing views in the literature [16], and hope that others will follow suit. [30] and asymmetry in the brain [38] in zebrafish, Drosophila border cells [31], and in collective migration of organisms. This study has considered collective cell migration, but the question of whether cell states are best described as discrete or continuous arises in many other biological problems.…”
Section: Discussionmentioning
confidence: 99%